2015
DOI: 10.1177/2055102915615046
|View full text |Cite|
|
Sign up to set email alerts
|

Put a limit on it: The protective effects of scarcity heuristics when self-control is low

Abstract: Low self-control is a state in which consumers are assumed to be vulnerable to making impulsive choices that hurt long-term goals. Rather than increasing self-control, the current research exploits the tendency for heuristic-based thinking in low self-control by employing scarcity heuristics to promote better consumption choices. Results indicate that consumers low in self-control especially benefited and selected more healthy choices when marketed as “scarce” (Study 1), and that a demand (vs supply) scarcity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…Scarcity heuristics exacerbate the development of consumer unease and fear during periods of crisis; so typically, mundane items see their value irrationally inflated and demand soar (Cheung et al 2015). Hence, herd mentality is perpetuated amongst typically rational consumers.…”
Section: Discussion On Herd Mentalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Scarcity heuristics exacerbate the development of consumer unease and fear during periods of crisis; so typically, mundane items see their value irrationally inflated and demand soar (Cheung et al 2015). Hence, herd mentality is perpetuated amongst typically rational consumers.…”
Section: Discussion On Herd Mentalitymentioning
confidence: 99%
“…Behavioural economics illustrates the effect of an information cascade, whereby consumers within a network are influenced by the behaviours and decisions of others (Easley and Kleinberg 2010). Furthermore, "scarcity heuristics" play further into the development of consumer fear during periods of shock, such that typically mundane items often see their value irrationally inflated through soaring demand (Cheung et al 2015). Historical examples of this irrational behaviour are widespread, with Yoon et al (2017) finding that upon Australian rice production falling 98% during the 2008 drought, consumers in Vietnam, India and Hong Kong began to stockpile rice due to fears of insufficient future supply and exacerbating the issue further; and after Japan's Fukushima Plant nuclear leak in 2011, consumers globally began purchasing products which had been rumoured to prevent or reduce radiation poisoning, including iodine tablets in Bulgaria, salt in China, and red wine and seaweed in Russia.…”
Section: Herd Mentalitymentioning
confidence: 99%
“…Considering the findings on low self-control and on how impulsivity is related to self-control [19,20], the present study aims at further understanding the relationship between the UPPS-P impulsivity traits and food choices, specifically under a nudging intervention. Based on certain study results [21][22][23], we expect higher impulsive individuals to rely more on heuristics when making decisions; therefore, we hypothesize that the higher an individual lies on the scale of impulsivity, the more their food choice will be affected by our nudging intervention. As only a couple of studies have investigated the effect of this specific nudging intervention, a secondary purpose of this study was to evaluate the effect of the nudging intervention, increasing perceived variety of vegetables, on increasing vegetable intake in a student population.…”
Section: Introductionmentioning
confidence: 99%
“…Self-control has been shown to play a role in influencing food choices, as seen in various studies. These studies suggest that when self-control is low, individuals have the tendency to rely more on impulsive decision-making strategies such as external, environmental cues or heuristics [15,[21][22][23]. Therefore, it can be suggested that food choices are mainly made through automatic processes, meaning they are driven more by impulsive tendencies rather than rational consideration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation